Biaya lingkungan dan sustainability report terhadap kinerja keuangan: Bukti empiris subsektor batubara di Bursa Efek Indonesia (2019–2024) - Helmi Nasrullah Muhammad; Fanda D. P. Rundengan (Yayasan Widyantara Nawasena Raharja, 2026)
Although the effect of green accounting on financial performance has been widely studied, research focusing specifically on the coal subsector, which faces higher environmental-regulation intensity and decarbonisation pressure than other mining subsectors remains limited. This study examines the effect of environmental costs and sustainability report disclosure on the financial performance of coal-subsector companies listed on the Indonesia Stock Exchange over the 2019–2024 period. A quantitative approach was applied using secondary data from financial statements and Corporate Social Responsibility (CSR) reports. From a population of 34 companies, 23 were selected through purposive sampling, yielding 115 firm-year observations. Multiple linear regression shows that environmental costs have a significant negative effect on Return on Assets (ROA), with a significance value of 0.001 (<0.05), whereas sustainability report disclosure has no significant effect (significance value 0.675 > 0.05). The two variables jointly explain only 8.9% of the variation in ROA (F-test significance 0.005 < 0.05). The findings underline the importance of managing environmental costs strategically to improve operational efficiency and profitability, and highlight the need for firms to integrate sustainability disclosure into their core business strategy.